Culture is an imperfect and heterogeneous reference standard in pediatric tuberculosis. (December 2016) - DiNardo, Andrew R.; Detjen, Anne; Ustero, Pilar; Ngo, Katherine; Bacha, Jason; Mandalakas, Anna M.
Abstract: Background: In pediatric tuberculosis (pTB), culture is the accepted reference standard for assessing new diagnostic tests despite culture only confirming 10–50% of clinically diagnosed cases. Methods: Using the studies previously included in the systematic review of Gene Xpert, we evaluated the diagnostic yield of culture. Children with symptoms and signs suggestive of TB were considered to have a clinical diagnosis if they were 1) culture positive or 2) followed clinically for at least one month and started on Anti-Tuberculosis Therapy (ATT). Results: Of 1989 children with presumptive pTB, 229 (11.5%) had culture-confirmation. Of the remaining 1760 culture negative children, 710 (24.4) were classified as culture-negative clinical TB and 821 were classified as "not TB". Diagnostic yield of culture was 24.4% (median 28.7% IQR 15.6%–42.4%; range 1.5%–65%). Conclusion: Culture, the accepted reference standard for pediatric TB diagnostics, has a low and variable yield that impacts how diagnostic studies should be reported as well as everyday clinical care.